2016
DOI: 10.1016/j.jpag.2016.01.036
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Treatment of Vaginal Venolymphatic Malformation With Sirolimus in a 2 Year Old Girl

Abstract: logistic regression was conducted to examine the odds of initiating the HPV vaccine series, after adjusting for age, race/ethnicity, insurance coverage, and belief that is acceptable for 16 year olds to have sex. Results: Among 235 sexually active US adolescent females surveyed, 62% initiated the HPV vaccine series after sexual debut. Compared with adolescent females who initiated the HPV vaccine series before sexual debut, those initiating the HPV vaccine series after sexual debut were significantly more like… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Through these methods, 20 articles were identified, containing a total of 71 cases in which sirolimus was used to treat lymphatic malformations, venolymphatic malformations, and capillary-lymphatico-venous malformations. 8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] After identifying these articles, all text and figures were carefully assessed for relevant data. The following information on study characteristics and clinical treatments was extracted from all included studies: publication metrics (name of first author and year of publication), subject information (age, gender, and localization of malformation), and treatment information (sirolimus dose, planned target trough level, treatment duration, treatment outcomes, additional therapies, and adverse events).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Through these methods, 20 articles were identified, containing a total of 71 cases in which sirolimus was used to treat lymphatic malformations, venolymphatic malformations, and capillary-lymphatico-venous malformations. 8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] After identifying these articles, all text and figures were carefully assessed for relevant data. The following information on study characteristics and clinical treatments was extracted from all included studies: publication metrics (name of first author and year of publication), subject information (age, gender, and localization of malformation), and treatment information (sirolimus dose, planned target trough level, treatment duration, treatment outcomes, additional therapies, and adverse events).…”
Section: Methodsmentioning
confidence: 99%
“…Fourteen studies commented on adverse events associated with and probably being a result of sirolimus therapy. 8,12,15,16,18,20,21,23,24,[26][27][28][29][30] In three studies patients (n = 5) experienced no side effects. 15,23,28 In the other 11 studies different adverse effects were reported.…”
Section: Adverse Effects Of Sirolimus Treatmentmentioning
confidence: 95%
See 3 more Smart Citations